2016
DOI: 10.1111/jop.12521
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of Cyclooxygenase‐2 in the pathogenesis of oral lichen planus – an immunohistochemical study with supportive histochemical analysis

Abstract: Interaction between upregulation of COX-2, mast cell and basement membrane sets a vicious cycle which relates to the chronic nature of the disease. Inhibitors of COX-2 may reduce the inflammatory process preceding the immune dysregulation in OLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…An important question concerns which of the inflammatory mediators found in OLP is responsible for the increased COX-2 expression. Relatively little work has been undertaken in this respect, but Singh et al, [37] reported a strong association of COX-2 immunoreactivity with both basement membrane integrity and the mast cell count in OLP. Mast cells are an important source of TNF-α, and so we were interested to determine whether the findings in OLP could be mimicked by treating cells with TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…An important question concerns which of the inflammatory mediators found in OLP is responsible for the increased COX-2 expression. Relatively little work has been undertaken in this respect, but Singh et al, [37] reported a strong association of COX-2 immunoreactivity with both basement membrane integrity and the mast cell count in OLP. Mast cells are an important source of TNF-α, and so we were interested to determine whether the findings in OLP could be mimicked by treating cells with TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…The slides were evaluated under bright field research microscope using computerized image software (NIS, Nikon) to provide morphometric analysis of COX‐2 expression. All tissue sections were observed under light microscope at ×100 magnification to determine the areas that presented with highest number of COX‐2 positive cells and then their quantification was done at ×400 magnification in five representative areas by predefined criteria (Singh et al, 2017). The degree of staining was scored as score 0, no positive cells; score 1, < 5% positive cells; score 2, 5%–30% positive cells and score 3 for>30% positive cells.…”
Section: Methodsmentioning
confidence: 99%
“…Along with the cells various enzymes like proteases, matrix metalloproteinases and cyclooxygenase (COX)‐2 are also involved in the pathophysiology of periapical lesions. COX‐2, induced in response to growth factors, hormones and cytokines is a plasma membrane bound enzyme that plays a key role in the growth and spread of inflammatory reactions and cystic processes (Álvares et al, 2018; Singh et al, 2017). It is thought to be involved in the pathogenesis of periapical lesions, nevertheless additional information is warranted to elucidate its role (AkbarzadehBaghban et al, 2017; Álvares et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation